Human health, ecological risk and heavy metal pollution assessment in Langat River by transplantation of Corbicula javanica - Wong, Koe Wei (2016)
Heavy metal pollution has become a major concern nowadays because these pollutants are not biodegradable and may be biomagnified and bioaccumulated and could potentially be harmful to biota over certain level. Therefore, assessment of the potential risks of heavy metal pollutions to ecosystem and human health are necessary. The freshwater bivalve clam Corbicula javanica (Family: Cyrenidae) is abundant, easily identifiable, sedentary life style and tolerant to the increased bioavailable heavy metals in the environment, besides having large enough for analysis and the potential to reflect bioavailability. Therefore, it is suitable to be a good biomonitor. The first objective of this study was to assess the heavy metal pollution in the Langat River by transplantation of C. javanica from upstream pristine site to downstream polluted sites of the river. The freshwater clams C. javanica was transplanted from upstream Pangsun (PS) to Semenyih (SM), Dusun Tua (DT) and Kajang (KJ). Heavy metal in C. javanica and surface sediments was analysed by using FAAS for Cu, Fe, Ni, Pb and Zn, and ICP-MS for As, Co, Cd, Cr and Mn. Besides, the geochemical speciation of the heavy metals in surface sediments were analysed by using sequential extraction technique (SET). The second objective was to determine the ecological risk assessment of heavy metals in the surface sediments of the Langat River by comparison with sediment quality guidelines (SQGs), and calculations of geoaccumulation index (Igeo), enrichment factor (EF), potential risk for individual metal (Er), potential ecological risk index (PERI) and combined pollution index (CPI). Lastly, the third determine the human health risk assessment via the consumption the clam collected from the transplantation study in the Langat River by comparison with food safety guidelines and calculation of estimated daily intake (EDI) and target hazard quotients (THQ). From the results, the higher concentration of Co, Cr, Fe, Mn, Ni and Zn in the sediment of PS, are associated with the periodic discharge of dam impoundment of Pangsun Dam. Higher As and Cd in SM, are related to the use of phosphate fertilizers and pesticides in the oil palm plantation nearby the particular site. Higher Pb, and Cu were KJ, are associated to the domestic waste emission in urban area. The clams‘ Total Soft Tissue (TST) has the ability to accumulate Fe, Zn, Cu, Mn, Co, Cr, As and Cd and the shell has the ability to accumulate higher level of Pb and Ni. The correlation analysis revealed that 8 metals (As, Co, Cr, Fe, Mn, Ni, Pb and Zn) in TST while 5 metals (As, Cd, Cr, Fe and Mn) in shell have positively and significantly correlation with respective metal concentration in sediment, indicating the clams is a good biomonitor of the metal levels. Geo-chemical fractions extraction revealed that As, Cr, Fe, Mn, Ni and Pb in the sediment were dominated by the resistant (R) fraction suggested that it may be less potentially bioavailable and be poorly mobilized. However, care should be taken for As since its concentrations are higher than previous studies. Zn and Cd were found to be abundant in Acid Reducible fraction (AR) in all sites, this indicated that these two metals were highly mobilized with potential environmental consequences. However, the impact might be limited since the concentration of Zn and Cd are not higher than previous studies. The difference in geochemical fraction distribution in Co indicates four sites may have different source. Cu in KJ are abundant in oxidizable-organic (OO) fraction. This indicates that the Cu in KJ were organic in nature and it is easily absorbed. Various geochemical indexes for a single metal pollutant (Igeo, EF, Cf, and Er) all agreed that Cd, Co, Cr, Cu, Fe, Mn, Ni and Zn are not likely to cause adverse effect to the river ecosystem, but As and Pb could pose a potential ecological risk to the river ecosystem. When all metals were accounted, all indexes (Cd, CPI and PERI) showed that overall metal concentrations in Langat River are still within safe limit. The values of EDI of C. javanica were found to be all lower than oral reference dose (RfD) guidelines for all metals. Furthermore, the calculated THQ and total THQ were found to be less than 1. Therefore, there will be no non-carcinogenic human health risk on both average and high level consumption of total soft tissue of C. javanica. The finding of present study indicated that TST and shell of C. javanica are good biomonitors of heavy metal bioavailability. We deduced that the elevated heavy metals of PS, SM and KJ are associated with dam discharge, use of fertilizers or pesticides and domestic waste discharge respectively. Ecological risk assessment indicated that most of the metals are unlikely to cause adverse effects except As and Pb. Human health risk assessment indicated that prolonged consumption of C. javanica in this river are safe.